The role of networks in accessing european funds aimed at the international development of INVs: an analysis of cases - Kulaga, Barbara; Cardinali, Silvio (Piccola Impresa / Small Business, 2022)
The ability to attract funds and to internationalize are among the main challenges for SMEs and this is even more evident for the International New Ventures (INVs) because of the so-called liabilities. In the literature one of the main mechanisms by which INVs try to deal with the lack of resources is the use of networks. This exploratory study contributes to the literature on network theory by interpreting and investigating the two-phase internationalization process (exploration and exploitation), from the point of view of INVs’ entrepreneurs; and fills a gap in the literature about the scarcity of studies on European funding instruments as resources for internationalization. The results, show that INVs use personal networks during exploration, business networks in exploitation and European funding via personal networks and thanks to knowledge gained in academia, in both phases to counteract the liability of foreignness, liability of smallness, and liability of newness.